Optimalisasi Sistem Pengarsipan File Digital Berbasis Web dengan Metodologi Waterfall di Rumah Sakit Umum Kabupaten Nabire - Theopilus Basten Imbiri; Usman Arfan (STMIK Pesat Nabire, 2026)
Digital transformation in archive management is an urgent need for public service institutions, including regional hospitals. This research aims to develop a web-based digital file archiving system at the Regional General Hospital (RSUD) of Nabire Regency using the Waterfall methodology. The system is designed to improve the efficiency and effectiveness of archive management, accelerate access to information, and minimize the risk of loss or damage to physical documents. The development stages include needs analysis, system design, implementation, testing with the Black Box method, and maintenance. The results of the implementation show that the system is able to accommodate archiving needs well, improve administrative performance, and support the digitalization of hospital services as a whole. The study also emphasizes the importance of training for users so that the system can be operated optimally, as well as integration with existing hospital information systems to ensure sustainability. Thus, this web-based digital filing system is expected to be a strategic solution in supporting more modern, transparent, and accountable public services in the regional hospital environment.